A161 EVALUATING THE DIFFERENCES IN PERCEIVED STRESS AMONG NON-INFLAMMATORY AND INFLAMMATORY IBD FLARES. (1st March 2018) - Hansen, T; Targownik, L; Walker, J R; Bernstein, M T; Sexton, K; Bernstein, C N
Abstract: Background: The presence and severity of symptoms in IBD correlate poorly with the degree of inflammatory activity, especially in Crohn's disease (CD). Psychological factors, including perceived stress and mood disruption are associated with symptom activity. This relationship is bidirectional with increased symptoms predicting later increased perceived stress and vice versa. It is unclear whether the association between high perceived stress and active symptoms is weighted more towards high perceived stress being associated with symptomatic activity in individuals and no concurrent active inflammation than it would be in persons with increased symptoms and evidence of intestinal inflammation. Aims: To evaluate whether perceived stress is associated with increased symptoms in non-inflammatory versus inflammatory IBD flares. Methods: We recruited 487 persons from the University of Manitoba IBD registry to assess the relationship between intestinal inflammation, symptomatic disease activity, and psychologic factors. Disease activity was assessed using the Harvey Bradshaw Index (HBI) for CD and the Powell Tuck Index (PTI) for UC. Perceived stress was measured using the Cohen Perceived Stress (CPSS) scale with high scores defined as ≥ 20. A fecal calprotectin (FCAL) level >250ug/g was the cut point for active inflammation. An inflammatory flare was defined as a FCAL > 250ug/g and disease index >4. A non-inflammatory flare was defined as FCAL ≤250 and disease activity index >4. Completed surveys and stool samples were submitted at baseline, 3 months and 6 months. Results: For CD (n=265), 31 (11.7%) were in an inflammatory flare at baseline while 55 (20.8%) were in a non-inflammatory flare. For UC (n=222) 32 (14.4%) were in an inflammatory flare while 39 (17.6%) were in a non-inflammatory flare. There was no significant difference in the likelihood of having a high CPSS score between those with inflammatory vs non-inflammatory flares either at baseline or at 6 months(Table 1). There were no differences in the scores on individual items in the CPSS score between persons in inflammatory flares versus those in non-inflammatory flares. Conclusions: Increased perceived stress is equally associated with increased symptoms with persons with IBD regardless of the presence of inflammatory activity. Funding Agencies: None